Gastric digestion of α-lactalbumin in adult human subjects using capsule endoscopy and nasogastric tube sampling. Issue 4 (26th June 2014) - Sullivan, Louise M.; Kehoe, Joseph J.; Barry, Lillian; Buckley, Martin J. M.; Shanahan, Fergus; Mok, K. H.; Brodkorb, André
Abstract : In the present study, structural changes in the milk protein α-lactalbumin (α-LA) and its proteolysis were investigated for the potential formation of protein–fatty acid complexes during in vivo gastric digestion. Capsule endoscopy allowed visualisation of the digestion of the test drinks, with nasogastric tubes allowing sampling of the gastric contents. A total of ten healthy volunteers had nasogastric tubes inserted into the stomach and ingested test drinks containing 50 g/l of sucrose and 25 g/l of α-LA with and without 4 g/l of oleic acid (OA). The samples of gastric contents were collected for analysis at 3 min intervals. The results revealed a rapid decrease in the pH of the stomach of the subjects. The fasting pH of 2·31 (sd 1·19) increased to a pH maxima of pH 6·54 (sd 0·29) after ingestion, with a subsequent decrease to pH 2·22 (sd 1·91) after 21 min ( n 8). Fluorescence spectroscopy and Fourier transform IR spectroscopy revealed partial protein unfolding, coinciding with the decrease in pH below the isoelectric point of α-LA. The activity of pepsin in the fasting state was found to be 39 (sd 12) units/ml of gastric juice. Rapid digestion of the protein occurred: after 15 min, no native protein was detected using SDS–PAGE; HPLC revealed the presence of small amounts of native protein after 24 min of gastric digestion. Mirocam ® capsule endoscopy imaging and video clips (see the online supplementary material) revealed that gastric peristalsis resulted in a heterogeneous mixture during gastric digestion. Unfolding of α-LA was observed during gastric transit; however, there was no evidence of a cytotoxic complex being formed between α-LA and OA.